Impacts of toxin production triggers on planktonic food web structure and environmental toxin loads: A theoretical approach - Lael Wakamatsu; Gregory L. Britten; Andrew M. Fischer; Christopher J.S. Bolch; Monique Messié (Harmful Algae, 2026)

Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

Giant predators, tiny pollutants: Exploring anthropogenic microparticles in the feces of white sharks (Carcharodon carcharias) - Gretchen K. Bielmyer-Fraser; Julia M. Courville; Morgan Vervaeke; Lisa A. Hoopes; Michael W. Hyatt; Brett McBride; G. Christopher Fischer; Alisa L. Newton (Environmental Pollution, 2026)

Linking Hydrological Pathways and Organic Matter Dynamics to Water Colour in Temperate Forested Catchments - Charuni Jayasekara; Felix Smalley; Philip Noske; Sarah Fischer; Thomas Keeble; Mariia Lukinykh; Christopher Sean Lyell; Patrick Lane; Gary Sheridan (Environmental Processes, 2026)
Water colour, derived from chromophoric dissolved organic matter (cDOM), is a key indicator of water quality. Increasing water colour trends worldwide and in Australia have raised concerns, yet the drivers of colour variability in natural ecosystems remain poorly understood. We aimed to investigate the drivers of spatial and temporal variability of water colour generation across well-drained temperate forested catchments in south-eastern Australia and tested its use as a proxy for dissolved organic carbon (DOC). Baseflow colour was measured across a diverse topographical range to model spatial variability, while automatic samplers captured temporal variability during rainfall events. Our spatial model explained 87% of the variability in colour, with vegetation type, aridity index, and maximum annual temperature as significant predictors. Highly productive sites located in higher-elevation, higher-rainfall areas may produce high colour year-round due to favourable moisture conditions and high litter production supporting microbial decomposition. Lower-productivity sites may exhibit low colour during low-rainfall periods due to limited water availability for microbial decomposition but may exhibit high colour during rainy seasons due to accumulated litter decomposing with increased moisture. Hysteresis analysis indicated the majority of anticlockwise loops, suggesting that colour comes from distant sources through sub-surface flow paths, while the discharge-colour relationship showed an asymptotic relationship, indicating a finite pool of soluble organic compounds available for leaching. Overall, low colour concentrations can be expected during drought periods, followed by considerably high colour concentrations with subsequent rains. Future research should focus on modelling colour production in these catchments under future predicted climate change scenarios.

Investigating wildfire smoke-related emergency department visits and syndromic surveillance in New Mexico 2019–2022 - Olivia Sablan; Bonne Ford; Colin B. Hawkinson; Leiqiu Hu; Jihoon Jung; Chelsea Eastman Langer; Courtney Maichak; Kamal Jyoti Maji; Stephanie Moraga-McHaley; Joseph O’Dell; Christopher K. Uejio; Melissa VanSickle; et al. (Air Quality, Atmosphere & Health, 2026)

Parallel elevational replacement of hosts and parasites in a highly susceptible songbird genus - Daniele L. F. Wiley; Jessie L. Williamson; Silas E. Fischer; Selina M. Bauernfeind; Henry M. Streby; Kathy Granillo; Christopher C. Witt; Lisa N. Barrow (Oecologia, 2026)

From simulation to sustainability: using forest growth models for indicator-based bioeconomy monitoring - Mirjam Pfeiffer; Rüdiger Grote; Joachim Rock; Mart-Jan Schelhaas; Andreas Huth; Sara Filipek; Christopher P. O. Reyer; Boris Sakschewski; Sarah Bereswill; Mats Nieberg; Jessica Hetzer; Tim Anders; et al. (Regional Environmental Change, 2026)

Intercomparison of Earth Observation products for hyper-resolution hydrological modelling over Europe - Almudena García-García; Pietro Stradiotti; Federico Di Paolo; Paolo Filippucci; Milan Fischer; Matěj Orság; Luca Brocca; Jian Peng; Wouter Dorigo; Alexander Gruber; Bram Droppers; Niko Wanders; et al. (Remote Sensing of Environment, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Future Climate and Land Use Change Will Equally Impact Global Terrestrial Vertebrate Diversity - Chantal Hari; Thomas Hickler; Christian Hof; Christopher P. O. Reyer; Inne Vanderkelen; Alke Voskamp; Matthias F. Biber; Markus Fischer; Édouard L. Davin (Global Ecology and Biogeography, 2026)
Aim Terrestrial biodiversity is impacted by both climate and land use change. Yet, future biodiversity projections have rarely considered these two drivers in combination. In this study, we aim to assess the individual and combined impact of future climate and land use change on global terrestrial vertebrate diversity under a ‘sustainability’ (SSP1‐RCP2.6) and an ‘inequality’ (SSP4‐RCP6.0) scenario. Location Global land, excluding Antarctica. Time Period 1995, 2080. Major Taxa Studied Amphibians, birds, and mammals. Methods We combined global climate‐driven species distribution model (SDM) projections of 13,903 vertebrates (amphibians, birds, and mammals) with future and present land use projections from the Land Use Harmonisation 2 (LUH2) project. We refined the SDM outputs by the habitat requirements of each species using a land use filtering approach. We then analyzed future species richness changes globally, per region, and per land use category, and looked at taxon‐specific effects. Results Under both scenarios, decreases in future species richness dominate at low and mid‐latitudes, with climate and land use change playing an equally important role. Land use change can be either an alleviating (SSP1‐RCP2.6) or an exacerbating (SSP4‐RCP6.0) factor of climate‐induced biodiversity loss. Sub‐Saharan Africa is projected to become a high‐risk area for future land use‐driven biodiversity loss under the SSP4‐RCP6.0. Under SSP1‐RCP2.6, forested and non‐forested land areas increase, while SSP4‐RCP6.0 leads to higher rates of deforestation and pasture expansion. Mammals experience the largest climate‐driven losses, affecting 56.4% of land area under SSP4‐RCP6.0, while amphibians are particularly vulnerable to land use‐driven losses, especially under SSP4‐RCP6.0. Main Conclusions Our results suggest that both climate and land use pressures on biodiversity will be highest in lower latitudes, which harbor the highest levels of biodiversity.

Predictions of southern migration timing in coastal sharks under future ocean warming - Maria H. Manz; Oliver N. Shipley; Robert M. Cerrato; Robert E. Hueter; Alisa L. Newton; John P. Tyminski; Bryan R. Franks; Tobey H. Curtis; Christopher Fischer; Joshua P. Zacharias; Christopher Scott; Keith J. Dunton; et al. (Conservation Biology, 2025)
Projected redistribution of marine species due to ocean warming may undermine current conservation efforts. Yet, there have been few studies on how ocean warming may alter migration timing. Across 5 years of acoustic telemetry data (2018–2022), we determined environmental drivers of southward migration timing for 6 migratory shark species from summer habitats in the Northwest Atlantic Ocean. We then forecasted how migratory timing from 3 regions, between the New England shelf and Mid‐Atlantic Bight, would respond under future sea surface temperatures (SSTs). Photoperiod and SST were strong predictors of southern migration in sharks, but the strength of these effects varied latitudinally. Overall, we found delayed departure dates from summer habitats under future elevated SSTs, indicating prolonged residency in northern habitats (median = ∼12 days). Sandbar sharks ( Carcharhinus plumbeus ) exhibited the largest delay in the onset of southern migrations (median = 29 days), whereas sand tiger sharks ( Carcharias taurus ) and white sharks ( Carcharodon carcharias ) exhibited the smallest delay (median = 1 day). Delays in migration timing of coastal shark species may alter local ecosystem dynamics and challenge current management strategies. These findings illustrate the utility of collaborative data‐sharing networks to expand understanding of broadscale animal movements and contribute to effective species management under a changing climate.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Do affluent neighbourhoods pay more for transit access? Exploring the capitalization of employment accessibility within different housing submarkets in Vancouver - Robert Nutifafa Arku; Christopher D. Higgins; Jaimy Fischer; Steven Farber (Journal of Transport Geography, 2024)

Quantifying the relative importance of biotic and abiotic factors in landscape-based models of stream fish distributions - Christopher A. Custer; Douglas P. Fischer; Geoffrey Smith; Aaron Henning; Megan Kepler Schall; Matthew K. Shank; Timothy A. Wertz; Tyler Wagner (Community Ecology, 2024)
Lotic fish species distributions are frequently predicted using remotely sensed habitat variables that characterize the adjacent landscape and serve as proxies for instream habitat. Recent advancements in statistical methodology, however, allow for leveraging fish assemblage data when predicting distributions. This is important because assemblage composition likely provides better information about instream habitat compared to landscape-derived metrics and therefore may improve predictions. To better understand the value of using multi-species fish data in species distribution modeling, we fit two conditional random fields (CRF) models to quantify the relative importance of fish assemblage co-occurrence, landscape-derived habitat variables, and interactions between these two predictor groups (i.e., effects of co-occurrence could be context-dependent) at over 1200 stream catchments in Pennsylvania, USA. We first compared predictive performance of CRF models against traditionally used single-species logistic regressions (generalized linear models; GLMs) and found that inclusion of fish assemblage data often improved predictive performance. The multi-species CRF models performed significantly better at predicting occurrence for 63% of species with an average percent increase in AUC of 25% compared to GLMs. Furthermore, the CRF identified species co-occurrences as more informative, and thus relatively more important, at predicting occurrence than the other effect types. The CRF also suggested that allowing these biotic effects to be context-dependent was important for predicting occurrence of many species. These findings illustrate the value of fish assemblage data for landscape-scale species distribution modeling and leveraging this information can improve predictions and inferences to help inform the management and conservation of freshwater fishes.

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Adoption and impacts of improved post-harvest technologies on food security and welfare of maize-farming households in Tanzania: a comparative assessment - Christopher Mutungi; Julius Manda; Shiferaw Feleke; Adebayo Abass; Mateete Bekunda; Irmgard Hoschle-Zeledon; Gundula Fischer (Food Security, 2023)
During the last decade, post-harvest losses (PHL) reduction has been topping the agenda of governments as a pathway for addressing food security, poverty, and nutrition challenges in Africa. Using survey data from 579 households, we investigated the factors that affect farmers’ decisions to adopt post-harvest technologies: mechanized shelling, drying tarpaulins, and airtight storage validated for reducing PHL in Tanzania’s maize-based systems, and the impacts on households’ food security and welfare. Mechanized shelling addressed a labor issue, while tarpaulins and airtight storage addressed product quality and quantity concerns. The results revealed large farm sizes and location in higher production potential zones (proxies for higher production scale) and neighbors' use of the technologies as universal drivers for adoption. Access to credit and off-farm income were unique determinants for airtight storage, while group membership increased the probability of adopting drying tarpaulin and airtight storage. The technologies have positive impacts on food security and welfare: drying tarpaulins and airtight storage significantly increased food availability (18–27%), food access (24–26%), and household incomes (112–155%), whereas mechanized shelling improved food and total expenditures by 49% and 68%, respectively. The share of total household expenditure on food decreased by 42%, 11%, and 51% among tarpaulin, mechanized shelling, and airtight storage adopter households, signaling significant improvements in food security and reductions in vulnerability. The results point to the need for policy support to enhance the adoption of these technologies, knowledge sharing among farmers, and financial resources access to support investments in the technologies.

Spatial analysis of mercury and stable isotopes in the vulnerable Dusky Grouper Epinephelus marginatus along the Brazilian coast - Mario V. Condini; Christopher R. Malinowski; David J. Hoeinghaus; Brittany L. Harried; Aaron P. Roberts; Brianne K. Soulen; Kathleen J. Roark; Alexis J. Khursigara; Luciano G. Fischer; Bianca Possamai; Maurício Hostim-Silva; Alexandre M. Garcia (Marine Pollution Bulletin, 2023)

Age class composition and growth of Atlantic cod (Gadus morhua) in the shallow water zone of Kongsfjorden, Svalbard - Markus Brand; Lisa Spotowitz; Felix Christopher Mark; Jørgen Berge; Erlend Lindau Langhelle; Jan Marcin Węsławski; Jane Aanestad Godiksen; Philipp Fischer (Polar Biology, 2023)
Although Atlantic cod has been observed in Svalbard waters since the 1880s, knowledge about the presence in the Arctic shallow water zone is limited. The regular catch of juvenile Atlantic cod in Kongsfjorden since 2008 is in line with an overall northward shift of boreal fish species toward the Arctic. This is the first study showing the age class composition, growth rates, and stomach content of Atlantic cod in the shallow water zone of Kongsfjorden, Svalbard. From 2012 to 2014 a total of 721 specimens were sampled in 3 to 12 m water depth. The primary age classes were identified as 0+, 1+, and 2+ using otolith age analysis. The different cohorts of these specimens show stable growth rates during the polar day and night. By stomach content analysis, we show that these specimens primarily feed on benthic food sources. These observations support the assumption that the shallow water zone of Kongsfjorden is likely to be a nursery ground for Atlantic cod.

The biome inventory – Standardizing global biogeographical land units - Jan‐Christopher Fischer; Anna Walentowitz; Carl Beierkuhnlein (Global Ecology and Biogeography, 2022)
Motivation The subdivision of the Earth's terrestrial surface into different biomes, ecozones, bio‐climatic realms or other large ecological land units is an essential reference for global biogeographical and ecological studies. Various classification schemes exist. These differ significantly in terms of the considered criteria for classification and the underlying methodology of class assignments. Evident divergences between global biome concepts are elusive, weakening hereon based analyses and assumptions. Compilation and standardization are essential for obtaining a framework that enables the comparison of different products. To address this need, we created a catalogue of standardized categorial biome maps comprising 31 different global products based on various methodological approaches. These products were processed individually to facilitate their use in large‐scale biogeographical and ecological analyses. Main types of variables contained We provide a unified RasterStack containing 31 terrestrial biome and land‐cover classifications in different layers. Additional ancillary and processing information is allocated. Spatial location and grain Global, 10 km × 10 km grain size in equal‐area Mollweide projection. Major taxa and level of measurement Biomes, ecozones, bio‐climatic zones, and ecological land units. Software format GeoTiff.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Unbound Brain-to-Plasma Partition Coefficient, Kp,uu,brain—a Game Changing Parameter for CNS Drug Discovery and Development - Irena Loryan; Andreas Reichel; Bo Feng; Christoffer Bundgaard; Christopher Shaffer; Cory Kalvass; Dallas Bednarczyk; Denise Morrison; Dominique Lesuisse; Edmund Hoppe; Georg C. Terstappen; Holger Fischer; et al. (Pharmaceutical Research, 2022)
Purpose More than 15 years have passed since the first description of the unbound brain-to-plasma partition coefficient (K p,uu,brain ) by Prof. Margareta Hammarlund-Udenaes, which was enabled by advancements in experimental methodologies including cerebral microdialysis. Since then, growing knowledge and data continue to support the notion that the unbound (free) concentration of a drug at the site of action, such as the brain, is the driving force for pharmacological responses. Towards this end, K p,uu,brain is the key parameter to obtain unbound brain concentrations from unbound plasma concentrations. Methods To understand the importance and impact of the K p,uu,brain concept in contemporary drug discovery and development, a survey has been conducted amongst major pharmaceutical companies based in Europe and the USA. Here, we present the results from this survey which consisted of 47 questions addressing: 1) Background information of the companies, 2) Implementation, 3) Application areas, 4) Methodology, 5) Impact and 6) Future perspectives. Results and conclusions From the responses, it is clear that the majority of the companies (93%) has established a common understanding across disciplines of the concept and utility of K p,uu,brain as compared to other parameters related to brain exposure. Adoption of the K p,uu,brain concept has been mainly driven by individual scientists advocating its application in the various companies rather than by a top-down approach. Remarkably, 79% of all responders describe the portfolio impact of K p,uu,brain implementation in their companies as ‘game-changing’. Although most companies (74%) consider the current toolbox for K p,uu,brain assessment and its validation satisfactory for drug discovery and early development, areas of improvement and future research to better understand human brain pharmacokinetics/pharmacodynamics translation have been identified.

Correction to: Ramisyllis kingghidorahi n. sp., a new branching annelid from Japan - M. Teresa Aguado; Guillermo Ponz‑Segrelles; Christopher J. Glasby; Rannyele P. Ribeiro; Mayuko Nakamura; Kohei Oguchi; Akihito Omori; Hisanori Kohtsuka; Christian Fischer; Yuji Ise; Naoto Jimi; Toru Miura (Organisms Diversity & Evolution, 2022)

Ramisyllis kingghidorahi n. sp., a new branching annelid from Japan - M. Teresa Aguado; Guillermo Ponz-Segrelles; Christopher J. Glasby; Rannyele P. Ribeiro; Mayuko Nakamura; Kohei Oguchi; Akihito Omori; Hisanori Kohtsuka; Christian Fischer; Yuji Ise; Naoto Jimi; Toru Miura (Organisms Diversity & Evolution, 2022)
Among over 20,000 species of Annelida, only two branching species with a highly modified body-pattern are known until now: the Syllidae Syllis ramosa McIntosh, 1879, and Ramisyllis multicaudata Glasby et al. (Zoological Journal of the Linnean Society, 164, 481–497, 2012). Both have unusual ramified bodies with one head and multiple branches and live inside the canals of host sponges. Using an integrative approach (combining morphology, internal anatomy, ecology, phylogeny, genetic divergence, and the complete mitochondrial genome), we describe a new branching species from Japan, Ramisyllis kingghidorahi n. sp., inhabiting an undescribed species of Petrosia (Porifera: Demospongiae) from shallow waters. We compare the new species with its closest relative, R. multicaudata ; emend the diagnosis of Ramisyllis ; and discuss previous reports of S. ramosa . This study suggests a much higher diversity of branching syllids than currently known. Finally, we discuss possible explanations for the feeding behaviour in the new species in relation to its highly ciliated wall of the digestive tubes (especially at the distal branches and anus), and provide a hypothesis for the evolution of branching body patterns as the result of an adaptation to the host sponge labyrinthic canal system.

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Decline in Atlantic wolffish Anarhichas lupus in the North Sea : Impacts of fishing pressure and climate change - Joanna K. Bluemel; Simon H. Fischer; David W. Kulka; Christopher P. Lynam; Jim R. Ellis (Journal of Fish Biology, 2022)
Anarhichas lupus is a boreo‐Arctic species with biological characteristics often associated with vulnerability to overexploitation. Although not commercially targeted in the North Sea, A. lupus is a bycatch species in mixed demersal fisheries. Here we provide an overview of the status of A. lupus in the North Sea, as observed from commercial landings and fishery‐independent trawl survey data. A. lupus was once common across much of the central and northern North Sea but, since the 1980s, have declined in abundance, demographic characteristics (reduced size) and geographical range, with the shallower and more southerly parts of its range most impacted. A. lupus is still relatively frequent in the northern North Sea, where fishing intensity, though decreasing, is high. Bycatch through fishing remains a potential threat and, considering the likely impacts of predicted climate change on cold‐water species, risks of further regional depletion and/or range contraction remain. Whether or not A. lupus is able to re‐establish viable populations in former habitat in UK coastal waters is unknown. Given the lack of data, the precautionary principle would suggest that manageable pressures be minimized where the species and its habitat are at risk of further impacts, and more regular assessments of population status be undertaken.

Modeling Fine-Scale Cetaceans’ Distributions in Oceanic Islands: Madeira Archipelago as a Case Study - Marc Fernandez; Filipe Alves; Rita Ferreira; Jan-Christopher Fischer; Paula Thake; Nuno Nunes; Rui Caldeira; Ana Dinis (Frontiers in Marine Science, 2021)
Species distributional estimates are an essential tool to improve and implement effective conservation and management measures. Nevertheless, obtaining accurate distributional estimates remains a challenge in many cases, especially when looking at the marine environment, mainly due to the species mobility and habitat dynamism. Ecosystems surrounding oceanic islands are highly dynamic and constitute a key actor on pelagic habitats, congregating biodiversity in their vicinity. The main objective of this study was to obtain accurate fine-scale spatio-temporal distributional estimates of cetaceans in oceanic islands, such as the Madeira archipelago, using a long-term opportunistically collected dataset. Ecological Niche Models (ENM) were built using cetacean occurrence data collected on-board commercial whale watching activities and environmental data from 2003 to 2018 for 10 species with a diverse range of habitat associations. Models were built using two different datasets of environmental variables with different temporal and spatial resolutions for comparison purposes. State-of-the-art techniques were used to iterate, build and evaluate the MAXENT models constructed. Models built using the long-term opportunistic dataset successfully described distribution patterns throughout the study area for the species considered. Final models were used to produce spatial grids of species average and standard deviation suitability monthly estimates. Results provide the first fine-scale (both in the temporal and spatial dimension) cetacean distributional estimates for the Madeira archipelago and reveal seasonal/annual distributional patterns, thus providing novel insights on species ecology and quantitative data to implement better dynamic management actions.

Three-Dimensional Movements and Habitat Selection of Young White Sharks (Carcharodon carcharias) Across a Temperate Continental Shelf Ecosystem - Rachel L. Shaw; Tobey H. Curtis; Gregory Metzger; Michael P. McCallister; Alisa Newton; G. Christopher Fischer; Matthew J. Ajemian (Frontiers in Marine Science, 2021)
As highly mobile predators with extensive home ranges, some shark species often utilize a continuum of habitats across the continental shelf ranging from the surf zone to the open ocean. For many species, these cross-shelf distributions can change depending on ontogeny or seasonal conditions. Recent research has confirmed a white shark ( Carcharodon carcharias ) summer nursery off Long Island, New York; however, habitat characterization of this nursery has not yet been conducted nor has fine-scale analysis of vertical behavior. Between 2016 and 2019, 21 young-of-the-year and juvenile white sharks were fitted with satellite and acoustic tags to examine distribution and selection for a suite of oceanographic variables during their late summertime (i.e., August to October) residence in the New York Bight. Horizontal position estimates were used to extract a suite of environmental measurements via remote sensing platforms and were linked with vertical profiles to produce three-dimensional movements for a subset of individuals also fitted with pop-up satellite archival tags ( n = 7). Sharks exhibited horizontal movements parallel to Long Island’s southern shoreline and coastal New Jersey, with distances from 0.1 to 131.5 km from shore. Log-likelihood chi-square analyses determined selection for waters with underlying bathymetry of 20–30 m, sea surface temperatures between 20.0 and 22.0°C, sea surface salinities between 31.0 and 32.0 ppt, and chlorophyll-a concentrations between 2.0 and 8.0 mg⋅m –3 . Multiple individuals also traversed the mid- to outer shelf region after leaving the Montauk tagging area. Vertical depth profiles illustrated oscillations between the surface and 199 m of water, with an average swimming depth of 9.2 ± 8.9 m. Water column temperatures during these oscillations ranged between 7.9 and 26.2°C (mean = 19.5 ± 2.0°C) with several individuals traversing highly stratified regions presumably associated with a mid-shelf cold pool adjacent to the Hudson Shelf Valley. These results suggest young white sharks exhibit connectivity between the immediate shoreline and mid-continental shelf region, where they play important ecological roles as predators on a variety of species. Our study improves characterization of essential fish habitat for young white sharks and provides new insights into their reliance on this productive continental shelf ecosystem.

Moisture in Metal Powder and Its Implication for Processability in L-PBF and Elsewhere - Pelle Mellin; Masoud Rashidi; Marie Fischer; Lars Nyborg; Lorenzo Marchetti; Christopher Hulme-Smith; Markus Uhlirsch; Annika Strondl (BHM Berg- und Hüttenmännische Monatshefte, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Inside-out sustainability: The neglect of inner worlds - Christopher D. Ives; Rebecca Freeth; Joern Fischer (Ambio, 2020)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Reconnecting with nature for sustainability - Christopher D. Ives; David J. Abson; Henrik von Wehrden; Christian Dorninger; Kathleen Klaniecki; Joern Fischer (Sustainability Science, 2018)

Evaluation of atmospheric correction and high-resolution processing on SeaDAS-derived chlorophyll- a : an example from mid-latitude mesotrophic waters - James M. Bramich; Christopher J. S. Bolch; Andrew M. Fischer (International Journal of Remote Sensing, 2018)

The self‐sabotage of conservation: reply to Manfredo et al. - Christopher D. Ives; Joern Fischer (Conservation Biology, 2017)
Article impact statement : To address conservation challenges conservation scientists must work to change social values.

Leverage points for sustainability transformation - David J. Abson; Joern Fischer; Julia Leventon; Jens Newig; Thomas Schomerus; Ulli Vilsmaier; Henrik von Wehrden; Paivi Abernethy; Christopher D. Ives; Nicolas W. Jager; Daniel J. Lang (Ambio, 2017)

The in vitro PIG-A gene mutation assay: glycosylphosphatidylinositol (GPI)-related genotype-to-phenotype relationship in TK6 cells - Christopher T. Krüger; Bettina M. Fischer; Olivier Armant; Volker Morath; Uwe Strähle; Andrea Hartwig (Archives of Toxicology, 2016)

Coastal fog during summer drought improves the water status of sapling trees more than adult trees in a California pine forest - Sara A. Baguskas; Christopher J. Still; Douglas T. Fischer; Carla M. D’Antonio; Jennifer Y. King (Oecologia, 2016)

Genomic sequencing reveals historical, demographic and selective factors associated with the diversification of the fire‐associated fungus Neurospora discreta - Pierre Gladieux; Benjamin A. Wilson; Fanny Perraudeau; Liliam A. Montoya; David Kowbel; Christopher Hann‐Soden; Monika Fischer; Iman Sylvain; David J. Jacobson; John W. Taylor (Molecular Ecology, 2015)
Delineating microbial populations, discovering ecologically relevant phenotypes and identifying migrants, hybrids or admixed individuals have long proved notoriously difficult, thereby limiting our understanding of the evolutionary forces at play during the diversification of microbial species. However, recent advances in sequencing and computational methods have enabled an unbiased approach whereby incipient species and the genetic correlates of speciation can be identified by examining patterns of genomic variation within and between lineages. We present here a population genomic study of a phylogenetic species in the Neurospora discreta species complex, based on the resequencing of full genomes (~37 Mb) for 52 fungal isolates from nine sites in three continents. Population structure analyses revealed two distinct lineages in South–East Asia, and three lineages in North America/Europe with a broad longitudinal and latitudinal range and limited admixture between lineages. Genome scans for selective sweeps and comparisons of the genomic landscapes of diversity and recombination provided no support for a role of selection at linked sites on genomic heterogeneity in levels of divergence between lineages. However, demographic inference indicated that the observed genomic heterogeneity in divergence was generated by varying rates of gene flow between lineages following a period of isolation. Many putative cases of exchange of genetic material between phylogenetically divergent fungal lineages have been discovered, and our work highlights the quantitative importance of genetic exchanges between more closely related taxa to the evolution of fungal genomes. Our study also supports the role of allopatric isolation as a driver of diversification in saprobic microbes.

Loss of Prion Protein Leads to Age-Dependent Behavioral Abnormalities and Changes in Cytoskeletal Protein Expression - Matthias Schmitz; Catharina Greis; Philipp Ottis; Christopher J. Silva; Walter J. Schulz-Schaeffer; Arne Wrede; Katharina Koppe; Bruce Onisko; Jesús R. Requena; Nambirajan Govindarajan; Carsten Korth; Andre Fischer; et al. (Molecular Neurobiology, 2014)

Amphiphilic triblock copolymers with PEGylated hydrocarbon structures as environmentally friendly marine antifouling and fouling-release coatings - Zhaoli Zhou; David R. Calabrese; Warren Taylor; John A. Finlay; Maureen E. Callow; James A. Callow; Daniel Fischer; Edward J. Kramer; Christopher K. Ober (Biofouling, 2014)

Blue EaLAMP—a specific and sensitive method for visual detection of genomic Erwinia amylovora DNA - Christian Gosch; Richard Alexander Gottsberger; Karl Stich; Thilo Christopher Fischer (European Journal of Plant Pathology, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Taxonomic and functional diversity of farmland bird communities across Europe: effects of biogeography and agricultural intensification - Irene Guerrero; Manuel B. Morales; Juan J. Oñate; Tsipe Aavik; Jan Bengtsson; Frank Berendse; Lars W. Clement; Christopher Dennis; Sönke Eggers; Mark Emmerson; Christina Fischer; Andreas Flohre; et al. (Biodiversity and Conservation, 2011)

Lithostratigraphy, magnetostratigraphy, and radiometric dating of the Stanislaus Group, CA, and age of the Little Walker Caldera - Christopher J. Pluhar; Alan L. Deino; Nathan M. King; Cathy Busby; Brian P. Hausback; Tracy Wright; Collin Fischer (International Geology Review, 2009)

Significance of summer fog and overcast for drought stress and ecological functioning of coastal California endemic plant species - Douglas T. Fischer; Christopher J. Still; A. Park Williams (Journal of Biogeography, 2009)
Aim Fog drip is a crucial water source for plants in many ecosystems, including a number of global biodiversity hotspots. In California, dozens of rare, drought‐sensitive plant species are endemic to coastal areas where the dominant summer moisture source is fog. Low clouds that provide water to these semi‐arid ecosystems through fog drip can also sharply reduce evaporative water losses by providing shade. We quantified the relative hydrological importance of cloud shading vs. fog drip. We then examined how both factors influence the range dynamics of an apparently fog‐dependent plant species spanning a small‐scale cloud gradient. Location The study area is on Santa Cruz Island off the coast of southern California. It is near the southern range limit of bishop pine ( Pinus muricata D. Don), a tree endemic to the coasts of California and Baja, Mexico. Methods We measured climate across a pine stand along a 7 km, coastal–inland elevation transect. Short‐term (1–5 years) monitoring and remote sensing data revealed strong climatic gradients driven primarily by cloud cover. Long‐term (102 years) effects of these gradients were estimated using a water balance model. Results We found that shade from persistent low clouds near the coast reduced annual drought stress by 22–40% compared with clearer conditions further inland. Fog drip at higher elevations provided sufficient extra water to reduce annual drought stress by 20–36%. Sites located at both high elevation and nearer the coast were subject to both effects. Together, these effects reduced average annual drought stress by 56% and dramatically reduced the frequency of severe drought over the last century. At lower elevation (without appreciable fog drip) and also near the inland edge of the stand (with less cloud shading) severe droughts episodically kill most pine recruits, thereby limiting the local range of this species. Main conclusions Persistent cloud shading can influence hydrology as much as fog drip in cloud‐affected ecosystems. Understanding the patterns of both cloud shading and fog drip and their respective impacts on ecosystem water budgets is necessary to fully understand past species range shifts and to anticipate future climate change‐induced range shifts in fog‐dependent ecosystems.

The influence of summertime fog and overcast clouds on the growth of a coastal Californian pine: a tree-ring study - A. Park Williams; Christopher J. Still; Douglas T. Fischer; Steven W. Leavitt (Oecologia, 2008)

The Combined Effects of Remnant Vegetation and Tree Planting on Farmland Birds - ROSS B. CUNNINGHAM; DAVID B. LINDENMAYER; MASON CRANE; DAMIAN MICHAEL; CHRISTOPHER MacGREGOR; REBECCA MONTAGUE‐DRAKE; JOERN FISCHER (Conservation Biology, 2008)
Biodiversity conservation on agricultural land is a major issue worldwide. We estimated separate and joint effects of remnant native woodland vegetation and recent tree plantings on birds on farms (approximately 500–1000 ha) in the heavily cleared wheat and sheep belt of southern Australia. Much of the variation (>70%) in bird responses was explained by 3 factors: remnant native‐vegetation attributes (native grassland, scattered paddock trees, patches of remnant native woodland); presence or absence of planted native trees; and the size and shape of tree plantings. In terms of the number of species, remnant native vegetation was more important than tree planting, in a 3:1 ratio, approximately. Farms with high values for remnant native vegetation were those most likely to support declining or vulnerable species, although some individual species of conservation concern occurred on farms with large plantings. Farm management for improved bird conservation should account for the cumulative and complementary contributions of many components of remnant native‐vegetation cover (e.g., scattered paddock trees and fallen timber) as well as areas of restored native vegetation.

Initiation of primary anti-vaccinia virus immunity in vivo - Matthew A. Fischer; Christopher C. Norbury (Immunologic Research, 2007)

Coastal Ocean Physics and Red Tides: An Example from Monterey Bay, California - John Ryan; Heidi Dierssen; Raphael Kudela; Christopher Scholin; Kenneth Johnson; James Sullivan; Andrew Fischer; Erich Rienecker; Patrick McEnaney; Francisco Chavez (Oceanography, 2005)

Mating system of the hermaphroditic coral-reef fish, Serranus baldwini - Christopher W. Petersen; Eric A. Fischer (Behavioral Ecology and Sociobiology, 1986)